Expression of Matrix Metalloproteinase-13 in Human Skin Melanoma Cancer Treated by Baccaurea angulata in vitro. (Journal of Basic and Applied Research in Biomedicine, 2022)
This study aims to explore the cytotoxicity effects of B. angulata whole fruits and berries as well as to identify the fruit’s probable role on the level of MMP-13 protein expressions in human cancer cells. Cytotoxicity effects of B. angulata were evaluated in vitro using skin melanoma (A375) through treatment with novel B. angulata fibers (whole fruit and berries) via direct contact method. The growth inhibitions of the samples were evaluated through Methylene Blue Assay (MBA) with incubation time of the fibers on cells at 24, 48 and 72 hours. The results showed significant inhibition of growth in all samples with B. angulata whole fruit exhibiting the highest level of inhibition at 72 hours (87.69 %) while its berries showed a reading of 86.16 %. Consequently, this study indicates that both whole fruit fibers and berries of B. angulata may have cytotoxic effects against human skin melanoma. The quantitative expressions of MMP-13 in A375 cell lines which were subjected to the specified amount of fibers were evaluated through ELISA analysis. The results showed no expression of MMP-13 proteins in A375 cells for both whole fruit fibers (-1217.9 pg/ml) and berries (-1222.9 pg/ml). Furthermore, the results of the ELISA analysis depict a probable regulative effect of the fibers toward MMP-13 protein expressions in cancer cells. Hence, it can be concluded that B. angulata fruit has the potential to be used as a new source of natural substitute for anticancer treatment. Moreover, further study is needed in order to find the specific bioactive compounds involved in the anticancer properties which may have been influential in the regulation of MMP-13 proteins that could be fundamental in future endeavors for prospective therapeutic applications.